Housing types, population attributes and the development path of housing in large cities – a case study of Zhengzhou, China - Shen, Zhifeng; Li, Jing; Siraj, Ahsan; Taneja, Shilpa; Li, Zhihui (International Journal of Strategic Property Management, 2023)
Large-city housing costs are commonly attributed to excessive investment or financialization of the property market. The primary cause of housing issues is the imbalance between housing supply and demand. In the context of the urban housing market, the dynamic matching of housing supply and population type plays a crucial role in promoting equilibrium, maximizing the effectiveness of the market’s long-term mechanism, and preserving the coordination and stability of the market. To illustrate this point, the paper analyzes the impact of different attributes of population on housing demand from the perspective of dynamic matching between population attributes and housing types. Taking Zhengzhou City in Henan Province as an example, we consider the relationship between population attributes and housing types in the past, construct a theoretical model of population and housing type and anticipate the future supply scale of various housing kinds. Ultimately, our findings provide a theoretical justification for curbing excessive financialization and housing bubbles in large cities. Furthermore, we propose a practical method for urban housing to return to the essence of life from the perspective of matching housing supply and demand.